1999
DOI: 10.1071/a98035
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with biological nitrogen fixation in dairy pastures in south-western Victoria

Abstract: A survey of 71 sites was conducted in the dairying districts of south-western Victoria in October 1994 to determine factors associated with nitrogen (N) fixation in white clover based pastures. Twenty-eight factors (environmental, microbiological, management, soil, and pasture) were considered in relation to 2 indicators of N fixation by white clover, %Ndfa (percentage of total plant N derived from the atmosphere, as determined by the 15N natural abundance method) and kg of N fixed per tonne herbage dry matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…The white clover inoculant strain (TA1) was shown to be less persistent in acid soil than five of six other strains in a field comparison on annual clovers (Watkin et al 2000), so this rhizobia may be relatively sensitive to low soil pH. Consistent with this, in the survey of Riffkin et al (1999a) clover dependence on N 2 fixation was negatively correlated with rhizobial numbers on light textured soils (mean pH 4.6) but not on medium textured soils (mean pH 4.9), and the amount of N 2 fixed positively correlated with soil pH on light but not medium textured soils. Although lucerne has been shown to 'select' compatible, effective rhizobia under acid soil conditions (Ballard et al 2003), N 2 fixation will most likely be suboptimal under the typical soil pH of Australian dairy farms.…”
Section: N 2 Fixation Soil Acidity and Salinitysupporting
confidence: 64%
See 2 more Smart Citations
“…The white clover inoculant strain (TA1) was shown to be less persistent in acid soil than five of six other strains in a field comparison on annual clovers (Watkin et al 2000), so this rhizobia may be relatively sensitive to low soil pH. Consistent with this, in the survey of Riffkin et al (1999a) clover dependence on N 2 fixation was negatively correlated with rhizobial numbers on light textured soils (mean pH 4.6) but not on medium textured soils (mean pH 4.9), and the amount of N 2 fixed positively correlated with soil pH on light but not medium textured soils. Although lucerne has been shown to 'select' compatible, effective rhizobia under acid soil conditions (Ballard et al 2003), N 2 fixation will most likely be suboptimal under the typical soil pH of Australian dairy farms.…”
Section: N 2 Fixation Soil Acidity and Salinitysupporting
confidence: 64%
“…trifolii strain TA1 became a benchmark organism, and studies deploying this strain of rhizobia developed into a voluminous literature internationally, but little of this relates to its field performance in N 2 fixation, particularly with the varieties of white clover grown in Australia. As far as I am able to ascertain this has in fact not been examined, although it has been shown to be less effective in N 2 fixation on clovers than a range of other field isolates on several occasions (see Brockwell and Gibson 1968;Riffkin et al 1999a). Under laboratory conditions Gibson et al (1975) found that very few field isolates could match its N 2 -fixing effectiveness.…”
Section: Inoculant Rhizobia For Perennial Trifolium Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary sources of variability in the application of the natural-abundance method include selection of reference species and the B values used (e.g., Ho¨gberg 1997, Boddey et al 2000. We measured B values specific to the legume species and varieties that we sampled, but there are problems with applying B values from pot experiments to field measurements of BNF, including differences in BNF efficiency among Rhizobium strains; for instance, we inoculated with one strain, though many different background populations are likely present in the field (Riffkin et al 1999).…”
Section: Management-environment Interactionsmentioning
confidence: 99%
“…In grasslands, plant species may affect microbial biomass and activity (5). Riffkin et al (42) showed that N 2 fixation is influenced by different soil factors, including soil texture. Cejudo and Paneque (9) and Limmer and Drake (29) suggested that the nitrogen status of the soil may also influence N 2 fixation by diazotrophs.…”
mentioning
confidence: 99%